Analysis of Publications on Journal Impact Factor Over Time - van Leeuwen, Thed N.; Wouters, Paul F. (Frontiers in Research Metrics and Analytics, 2017)
In this paper we present the results of an analysis that describes the research centred around Journal Impact Factors. The purpose of the analysis is to make a start of studying part of the field of quantitative science studies that relates to the most famous and classic bibliometric indicator around, and see what characteristics apply to the research on Journal Impact Factors. In this paper we start with a general description of the research, from the perspective of the journals used, the fields in which research on Journal Impact Factors appeared, and the countries that contribute to the research on Journal Impact Factors. Finally, the paper presents a first attempt to describe the coherence of the field, which will form the basis for next steps in this line of research on Journal Impact Factors.